Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP Negeri Sekon Pada Materi Sistem Persamaan Linear Dua Variabel - Ruing, Lusisita Enjelita K; Mone, Ferdinandus; Bone, Dominifridus (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2024)
This research aims to describe students' mathematical problem solving abilities in the material on systems of linear equations in two variables (SPLDV) class VIII SMPN Sekon. This research was carried out in the odd semester of the 2023/2024 academic year in Sekon. The population in this study were all students in class VIII of Sekon State Middle School with a sample size of 22 students. The research instrument used was a test of conceptual understanding ability and mathematical problem solving ability. The research method used is a qualitative research design. Data were analyzed using data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that students with high level problem solving abilities are students who can work on and explain again what has been done according to the existing problem solving stages, while students with medium level problem solving abilities are students who can work on half of the questions. given and can explain again according to the stages of the questions that have been worked on and for students with low level problem solving abilities, these are students who can only understand the problem in the question but cannot carry out the calculation process to the final stage or conclusion and are also not able to explain again what was said. already written